Simultaneous determination of picomolar level of dissolved silver with other key trace metals in seawater samples using solid phase extraction and isotope dilution methods - Wong, Kuo Hong; Keisuke, Nishitani; Hajime, Obata; Hideki, Fukuda; Hiroshi, Ogawa; Farah Akmal, Idrus; Fatimah A'tirah, Mohamad; Asami S., Mashio; Hiroshi, Hasegawa (Elsevier B.V., 2024)
Simultaneous determination of dissolved silver (dAg) with other key GEOTRACES trace metals is difficult because dAg in seawater tends to form negatively charged chloride species that result in only 75% recovery efficiency with commonly used NOBIAS PA-1 chelating resins. In this study, we developed a method using solid phase extraction coupled with isotope dilution that enables full quantification (97.9 ± 2.1%) of dAg along with other major trace metals including cadmium (Cd), copper (Cu), manganese (Mn), nickel (Ni), and lead (Pb) (recovery efficiency = 100% to 102%) in seawater samples. Seawater samples were first spiked with Ag-109 and allowed to reach isotopic equilibrium before extraction using NOBIAS PA-1 chelating resin. Then, dAg isotope ratios (Ag-109/Ag-107) before and after solid phase extraction were determined and used to quantify dAg. Determination of dAg with dissolved Cd, Cu. Mn, Ni, and Pb in reference seawater material CASS-6 resulted in deviations of between 1.0% and 8.8% from the consensus values, which are well within the standard error of measurement. We then successfully determined the concentrations of dissolved Cd (0.05–0.2 nM), Cu (0.5–13 nM), Mn (10–140 nM), Ni (2–12 nM), Pb (5–110 nM), and Ag (10–40 pM) in Otsuchi Bay, Japan and its surrounding rivers. Evaluation of the behavior of dAg under a salinity gradient using estuarine samples collected from Samunsam River, Malaysia shows increasing dAg concentration with salinity (R2 = 0.68), which suggests release of sedimental Ag under high ambient chloride concentrations. Our new method enables rapid and simultaneous measurements of dAg with other key GEOTRACES trace metals in a sin.